THE RELATIONSHIP BETWEEN FINANCIAL EXCLUSION AND POVERTY ALLEVIATION IN BENIN - O, Timothy, P. (Economics and Statistics Research Journal (ESRJ), 2022)
This study aims to analyze the relationship between financial exclusion and poverty reduction in Benin. The study uses data from the World Bank’s Global Findex database for the years 2011, 2014, and 2017, and employs a probit model to determine factors contributing to financial exclusion, including lack of documentation, expensive financial services, distance from financial institutions, and lack of trust in financial institutions. The study also explores how individual characteristics such as age, education level, religion, gender, and employment status are associated with financial exclusion. The findings of the study reveal a positive and significant impact of financial exclusion on poverty and demonstrate that access to financial services can contribute to poverty reduction by providing entrepreneurial opportunities and reducing barriers to economic transactions. Additionally, the study provides a composite measure of financial inclusion and computes a financial exclusion index to assess its impact on poverty. The results suggest that despite recent improvements in access to financial services in rural areas of Benin, access to formal financial institutions remains a challenge for vulnerable groups and small- and medium-sized enterprises. This paper contributes to the literature on the impact of financial inclusion on poverty in Africa by investigating the effect of financial exclusion on poverty in Benin. The study emphasizes the importance of promoting financial inclusion and reducing financial exclusion as a means of reducing poverty in Benin and in similar developing countries